2006
DOI: 10.1111/j.1745-7262.2006.00120.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased expressions of vascular endothelial growth factor (VEGF), VEGF-C and VEGF receptor-3 in prostate cancer tissue are associated with tumor progression

Abstract: Increased expressions of VEGF and VEGF-C were closely associated with progression of PCa. The main contribution of increased VEGF expression for PCa progression was to upregulate MVD, which maintained the growth advantage of tumor tissue. However, the chief role of increased expressions of VEGF-C and VEGFR-3 was to enhance lymphangiogenesis and provide a main pathway for cancer cells to disseminate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 15 publications
0
29
0
1
Order By: Relevance
“…The expression of VEGFR-3 in colorectal tumour tissue was higher than it was in matched normal tissue Su et al (2006) Prostate cancer Significantly upregulated expressions of VEGF-A, VEGF-C, and VEGFR-3 were all found in malignant epithelium/ cancer cells compared with adjacent benign epithelium (Po0.01) Patients in stage D had a significantly higher score than did patients in stage A, B, or C when comparing the expression of VEGF-C or VEGFR-3 in the tumour area (Po0.01) Yang et al (2006) The increased expression of the VEGF-C /VEGFR-3 axis played a role in prostate cancer progression and in metastasis to regional lymph nodes Jennbacken et al (2005) VEGFR-3 expression was associated with tumour progression and may play an important role in facilitating the lymphatic spread of prostate carcinomas; a high level of VEGFR-3 in prostate cancer cells increases the risk of biochemical recurrence in prostate cancer patients treated by radical prostatectomy Li et al (2004) Kaposi sarcoma The VEGF-C/VEGFR-3 axis stimulates the migration and proliferation of Kaposi sarcoma cells Marchio et al (1999) Head and neck squamous cell carcinoma…”
Section: Gastric Cancermentioning
confidence: 98%
“…The expression of VEGFR-3 in colorectal tumour tissue was higher than it was in matched normal tissue Su et al (2006) Prostate cancer Significantly upregulated expressions of VEGF-A, VEGF-C, and VEGFR-3 were all found in malignant epithelium/ cancer cells compared with adjacent benign epithelium (Po0.01) Patients in stage D had a significantly higher score than did patients in stage A, B, or C when comparing the expression of VEGF-C or VEGFR-3 in the tumour area (Po0.01) Yang et al (2006) The increased expression of the VEGF-C /VEGFR-3 axis played a role in prostate cancer progression and in metastasis to regional lymph nodes Jennbacken et al (2005) VEGFR-3 expression was associated with tumour progression and may play an important role in facilitating the lymphatic spread of prostate carcinomas; a high level of VEGFR-3 in prostate cancer cells increases the risk of biochemical recurrence in prostate cancer patients treated by radical prostatectomy Li et al (2004) Kaposi sarcoma The VEGF-C/VEGFR-3 axis stimulates the migration and proliferation of Kaposi sarcoma cells Marchio et al (1999) Head and neck squamous cell carcinoma…”
Section: Gastric Cancermentioning
confidence: 98%
“…In addition, studies have shown that numerous cancer cells express Flt-4 (i.e., VEGFR-3), which plays an important role in tumor progression. Clinical trials in many human malignant tumors have shown that VEGFR-3 expression in cancer cells is correlated to the clinical stage of cancer in patients, the degree of cell differentiation, lymph node metastasis and patient prognosis (7)(8)(9). Van Trappen et al reported that VEGFR-3/Flt-4 expression levels changed with the progression of cervical intraepithelial carcinoma into cervical cancer (10).…”
Section: Clinicopathological Factors N Vegfr-3/flt-4 Mvd [Mean (Sd)] mentioning
confidence: 99%
“…Overexpression of vascular endothelial growth factor C (VEGF-C) has been detected in numerous cancers (34)(35)(36)(37), and the role of VEGF-C in promoting lymphatic metastasis has been demonstrated in several VEGF-C overexpression animal models of mammary carcinoma (38)(39)(40). Previous study revealed that Six1 could coordinate with transforming …”
Section: Six1 Expression N -----------------------------------------mentioning
confidence: 99%